Holocene climate change in southernmost South Africa: rock hyrax middens record shifts in the southern westerlies - (:unkn) unknown (My University, 2013)
South Africa's southern coastal margin is recognised as being a highly dynamic climatic region that plays a critical role in both regional and global atmospheric and oceanic circulation dynamics. Our understanding of the past dynamics of this system, however, has been limited by the number and nature of datasets available that can be used to infer changes in key climatic parameters in the region. In this paper we present new high resolution d 13 C and d 15 N data from two independently dated rock hyrax (Procavia capensis) middens from Seweweekspoort in South Africa's Groot Swartberg mountains. These data provide information regarding both past vegetation and hydroclimatic change, and allow a regional integration of available data that explore the long-term dynamics of mid-latitude circulation systems in the African sector of the Southern Hemisphere. Combined, a negative relationship is apparent between temperature and humidity in this area of the southern Cape, and these changes can for the first time be clearly linked to variations in Antarctic sea-ice extent and shifts in the southern westerly storm track. This dynamic is particularly evident between 5 and 7 cal kBP, when a reduction in sea-ice extent and a southward shift of the westerlies are manifested regionally by increased temperatures and a phase of marked aridity.
Keywords: African Research